Stress Responses Elicited by Misfolded Proteins Targeted to Mitochondria. Issue 12 (30th June 2022) - Narayana Rao, Kannan Boosi; Pandey, Pratima; Sarkar, Rajasri; Ghosh, Asmita; Mansuri, Shemin; Ali, Mudassar; Majumder, Priyanka; Ranjith Kumar, K.; Ray, Arjun; Raychaudhuri, Swasti; Mapa, Koyeli
Graphical abstract: Highlights: Proteotoxic stress in Mitochondrial Inter-membrane Space (IMS) and matrix leads to growth arrest of yeast cells. Proteotoxic stress in mitochondrial IMS or matrix leads to altered mitochondrial morphology (increased fragmentation). Mitochondrial respiratory chain complexes are downregulated and respiration is abrogated as an adaptive response to proteotoxic stress in the organelle. Apart from generalized response of proteotoxic stress in mitochondria, there are specific signatures of mitochondrial IMS and matrix specific proteotoxic stress responses. TOM complex components display specific modulatory role during IMS proteotoxic stress while Vms1 plays specific modulatory function on matrix proteotoxic stress response. Abstract: The double-membrane-bound architecture of mitochondria, essential for ATP production, sub-divides the organelle into inter-membrane space (IMS) and matrix. IMS and matrix possess contrasting oxido-reductive environments and discrete protein quality control (PQC) machineries resulting inherent differences in their protein folding environments. To understand the nature of stress response elicited by equivalent proteotoxic stress to these sub-mitochondrial compartments, we took misfolding and aggregation-prone stressor proteins and fused it to well described signal sequences to specifically target and impart stress to yeast mitochondrial IMS or matrix. We show, mitochondrial proteotoxicity leads to growth arrest of yeast cells of varying degrees depending on nature of stressor proteins and the intra-mitochondrial location of stress. Next, by employing transcriptomics and proteomics, we report a comprehensive stress response elicited by stressor proteins specifically targeted to mitochondrial matrix or IMS. A general response to proteotoxic stress by mitochondria-targeted misfolded proteins is mitochondrial fragmentation, and an adaptive abrogation of mitochondrial respiration with concomitant upregulation of glycolysis. Beyond shared stress responses, specific signatures due to stress within mitochondrial sub-compartments are also revealed. We report that stress-imparted by bipartite signal sequence-fused stressor proteins to IMS, leads to specific upregulation of IMS-chaperones and TOM complex components. In contrast, matrix-targeted stressors lead to specific upregulation of matrix-chaperones and cytosolic PQC components. Finally, by systematic genetic interaction using deletion strains of differentially upregulated genes, we found prominent modulatory role of TOM complex components during IMS-stress response. In contrast, VMS1 markedly modulates the stress response originated from matrix.